Exploring the causal influence of beliefs on mathematical competencies using an integrated approach of Interval-valued Intuitionistic Fuzzy Relational Map and TOPSIS - et. al., S. Arokiamary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Achievement in mathematics is widely recognised as a sign of intelligence and cognitive development. Students’ involvement in acquiring mathematical competencies is not just automatic, but needs conscious efforts from the part of students. The intrinsic factor that motivates the students to plunge into activities that develop mathematical competencies is self-belief or belief system. The relationship between personal beliefs and competencies acquired is so important that it attracts the interest of researchers to create an ‘intellectual and competent’ community. In this paper, the causal influence of mathematics related beliefs on mathematical competencies is studied using a hybrid fuzzy model called IVIFRM-TOPSIS. This expert based method is more comprehensive in its approach as the uncertain information is modelled with interval-valued intuitionistic fuzzy sets. This study exhibits the efficiency of the fuzzy hybrid model in analysing the causal relationship and ranking the order of influence.